2012
DOI: 10.1111/j.1600-6143.2011.03882.x
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Damage During Organ Recovery in Donation After Circulatory Death Donors: Data From UK National Transplant Database

Abstract: During the last 10 years, kidneys recovered/ transplanted from donors after circulatory death (DCD) have significantly increased. To optimize their use, there has been an urgent need to minimize both warm and cold ischemia, which often necessitates more rapid removal. To compare the rates of kidney injury during procurement from DCD and donors after brain death (DBD) organ donors. A total of 13 260 kidney procurements were performed in the United Kingdom over a 10-year period (2000-2010). Injuries occurred in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 9 publications
(9 reference statements)
3
41
1
Order By: Relevance
“…Alternatively, the small numbers of organs removed en bloc may have reduced the ability of this analysis to detect a truly reduced injury rate. Deceased donor type was not a risk factor for pancreas damage, unlike kidney or liver procurement where DCD donors appear to have higher rates of injuries (10,13). This finding is difficult to explain, but it is reassuring given the high proportion of DCD pancreas donors in the UK and their acceptable short-term outcomes (4,19).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Alternatively, the small numbers of organs removed en bloc may have reduced the ability of this analysis to detect a truly reduced injury rate. Deceased donor type was not a risk factor for pancreas damage, unlike kidney or liver procurement where DCD donors appear to have higher rates of injuries (10,13). This finding is difficult to explain, but it is reassuring given the high proportion of DCD pancreas donors in the UK and their acceptable short-term outcomes (4,19).…”
Section: Discussionmentioning
confidence: 91%
“…Although large analyses of procurement-related surgical injuries have been undertaken for the liver (7-10) and kidney (11)(12)(13), previous reports on pancreatic injuries in solid organ transplantation have come from small series only (14,15). In this study, the UK Transplant Registry was analyzed to determine the frequency of pancreatic injuries during procurement, identify factors associated with damage, and assess the impact of procurement injuries on pancreas allograft survival.…”
Section: Introductionmentioning
confidence: 99%
“…The standard ('super-rapid') technique is to quickly perform a laparotomy, cannulate the distal aorta, occlude the thoracic aorta, and perfuse the abdominal organs with cold preservation solution; the organs are then removed. Organ damage and resultant discard are higher in DCD compared to DBD donors; a study from the UK in 2012 showed an 11.4 % kidney injury rate during retrieval in DCD compared to 6.8 % during DBD retrieval [24]. This is not surprising, as during retrieval from a DCD donor there is no cardiac output and therefore it is more difficult to identify arteries.…”
Section: Organ Retrievalmentioning
confidence: 74%
“…Surgical injuries were more frequently observed during single-organ procurements than during multi-organ procurements: 8.2% vs 3.7%, respectively (p < 0.05) [7]. Similarly, injuries were more frequent seen during donation after circulatory death (DCD) then donation after brain death (DBD) procurement: (11.4% vs. 6.8%, p < 0.001) respectively [8]. Surgical damage was also seen with a less experienced surgeon (<30 organ vs >30 procurements: 12% vs 3% respectively, p < 0.01) [7].…”
Section: Discussionmentioning
confidence: 89%